The Influence of the Addressee in the Speech Industry among Ancient Arabic Scholars (The International Journal of Educational Sciences and Arts, 2024)
The term Speech Industry is a broad term, as it means authorship in its broadest sense. With the term Speech Industry, we are talking about the statement of the preacher, the poet, the transmitter, and the writer. The topic is ramified and contains long words. It is found in ancient Arabic references and books such as Al-Bayan and Al-Tabyeen by Al-Jahiz, Al-Sana’atayn book by Al-Askari, Al-Kala’i’s book Ahkam San’at Al-Kalam, and many others. In this paper, we try to shed light on an important joint of the topic of speech-making, which is the impact of the addressee on it, as explained by ancient Arabic scholars and those interested in studying the Arabic statement. Himself in it, whether the speech   is heard or read.
Keywords: Addressees; Speech; Industry; Scientists